Screw Press Machine Damage Analysis with Failure Mode and Effect Analysis (FMEA) Method in Palm Oil Factory PT. Socfindo Seunagan - Abdul Rauf; Sulaiman Ali; Joli Supardi (Jurnal Inotera, 2022)
PT. Socfindo is an industry engaged in the processing of Fresh Palm Fruit Bunches into crude palm oil or CPO (Crude Palm Oil). the day in the morning, therefore it is necessary to identify the presence of machine components that are prone to damage (critical components) and special actions are needed to take special actions against critical parts on the machine, by practicing the Predictive Maintenance Program or prevention. Simulation techniques, often known as Monte Carlo simulations, estimate reliability using random sampling of scenarios. Failure mode and effect analysis (FMEA) is defined as a process used to determine the actions that should be taken to ensure that each physical item or system can run properly according to the intended use by the user. Based on the information obtained, the RPN value of the Rubber Coupling Bush is 18, the RPN value of the Worm Screw is 126, the RPN value of the Press Cage is 72, the Adjusting Cone RPN value is 108, the Tie Rod Nut RPN value is 15, the Drive Shaft RPN value is 168, the Bearing RPN value is 12, the Motor Base RPN value is 15.